2019
DOI: 10.1002/jbm4.10250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Administration of Parathyroid Hormone and Parathyroid Hormone‐Related Protein on Fracture Healing: A Narrative Review of Animal and Human Studies

Abstract: Intermittent administration of parathyroid hormone (PTH) stimulates skeletal remodeling and is a potent anabolic agent in bone. PTH‐related protein (PTHrP) is anabolic acting on the same PTH1 receptor and is in therapeutic use for osteoporosis. The body of literature for PTH actions in fracture healing is emerging with promising yet not entirely consistent results. The objective of this review was to perform a literature analysis to extract up‐to‐date knowledge on the effects of intermittent PTH and PTHrP ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 141 publications
(266 reference statements)
0
24
1
Order By: Relevance
“…Thus, callus formation is essential for fracture healing. The intermittent administration of PTH has been shown to increase callus volume by increasing numbers of chondro- and osteo-progenitors at the bone fracture site in rats 22 , resulting in enhanced fracture healing 14 . While ALN does not enhance fracture healing, it also exerts no negative effect 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, callus formation is essential for fracture healing. The intermittent administration of PTH has been shown to increase callus volume by increasing numbers of chondro- and osteo-progenitors at the bone fracture site in rats 22 , resulting in enhanced fracture healing 14 . While ALN does not enhance fracture healing, it also exerts no negative effect 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that intermittent administration of PTH promoted bone formation during osseous wound healing 11,12 and boosted bone anabolism when administered during growth 13 . Furthermore, intermittent administration of PTH greatly accelerates callus formation during fracture healing in animals 14 . The antiresorptive treatment by ALN has no negative effect on the healing of tibial osteotomies and hip fractures [15][16][17] .…”
mentioning
confidence: 98%
“…In fact, osteoclast formation is essential for the anabolic activity of PTH in bone. 13 , 36 Interestingly, Kindlin-2 and PTH1R cooperatively regulate not only the osteoblast-mediated bone formation, but also the osteoclast formation in bone. While Kindlin-2 loss in osteoblastic cells increases the basal level osteoclast formation in bone, which is consistent with our previously published results, 30 it abolished the intermittent PTH stimulation of osteoclast formation in bone, which can be partially explained by the fact that intermittent PTH induces expression of RANKL in control but not cKO bones.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent administration of PTH, a treatment for severe osteoporosis approved by the United States Food and Drug Administration, increases the bone mass and bone mineral density (BMD) and improves bone microstructure in a number of animal models and in humans. 13 PTH exerts its anabolic activity in bone through the action of PTH1R that is primarily expressed in cells of the osteoblastic lineage. PTH promotes the mesenchymal stem cell (MSC) differentiation into osteoblasts and subsequent osteoblast proliferation and differentiation and inhibits osteoblast apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Both PTHrP and PTH bind to type 1 PTH receptor (PTHR1). Unlike PTH generated from parathyroid glands, PTHrP is produced by mesenchymal stem cells, certain tumors (squamous cell cancer of the lung, breast cancer, renal carcinoma, and prostate cancer) (Martin & Johnson, 2019; R. Zhang et al., 2019), and many other cell lines (keratinocytes, vascular smooth muscle cells, neurons, astrocytes, schwann cells, osteocytes, chondrocytes, and beta cells of the pancreas) (Funk et al., 2001; Macica et al., 2006; Martin, 2016; Shepherd et al, 2018; Weir et al., 1990; Yamashita & McCauley, 2019). The PTHrP peptide fragments consist of an N‐terminal (amino acids 1–36), mid‐region (37–86), nuclear localization sequence (NLS) (87–107), and C‐terminal region (108–139).…”
Section: Introductionmentioning
confidence: 99%